Trade and growth: Is Sub-Saharan Africa different? - Vincent Leyaro; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2010)
This paper argues that SSA has derived a minimal growth benefit from trade because of what it exports and that the detrimental effect of primary commodity export dependence on SSA growth can be captured by two structural variables, natural barriers to trade (NBT, trade costs) and natural resource endowments (NRE, primary commodity dependence). The analysis is based on a large panel of developing countries for 1970 to 2008 and explicitly tests for threshold effects in the structural variables. We find that high trade costs and natural resource endowments have a negative effect on growth and that the combination of these two factors accounts for the SSA dummy: SSA countries tend to have high values of NRE and NBT and this helps to explain why SSA countries experienced lower growth than other developing countries (the significant negative dummy for SSA). The trade variables also performed as expected. Exports and trade openness generally contribute to growth, but their effect on growth is affected by the structural variables; specifically high values as observed in SSA dampen the positive impact of trade on growth. The poor growth of SSA relative to other regions is largely accounted for by the combination of natural resource endowments and high transport costs so that the dependence on primary commodity exports has not supported growth.
Keywords: F10; F43; O40; O55; 330; Trade and Growth; Natural Barriers to Trade; Primary Commodity Exports; Sub-Saharan Africa; Außenwirtschaft; Rohstoff; Außenhandel; Wirtschaftswachstum; Afrika südlich der Sahara